The Influence of Using Audiovisual Media on the Understanding and Application of Poetry Writing Skills for Class XI TKJ 1 SMK Negeri 3 Gunungsitoli Students - Riana, Riana (Mahesa Research Center, 2024)
This examination is entitled The Impact of Utilizing General Media on the Survey Text Composing Abilities of Class XI Understudies at SMKN 3 Gunung Sitoli. The point of this examination was to determine the impact of utilizing general media on the verse-composing abilities of class XI understudies at SMKN 3 Gunung Sitoli. The methodology utilized in this exploration is quantitative and unmistakable, utilizing a trial model with a benchmark group pre-test and post-test plan. The information source or exploration object in this examination is all female class XI TKJ understudies, comprising of 2 classes with a total of 27 understudies, and every one of them is utilized as an examination object. Class XI MM is the control class, and class XI TKJ is the trial class. Information assortment strategies utilize starting tests (pre-test) and last tests (post-test). The examination results show contrasts in the normal pre-test and post-test scores for the exploratory and control classes. The normal pre-test score for the control class was 78.44, while the score for the post-test results was 89.78. The typical score (mean) in the trial-class pre-test results was 68.22, while the post-test results were 90.89. These outcomes show that there is a critical impact of the utilization of general media on verse composition abilities; all in all, Ha is acknowledged and H0 is dismissed.